Ampliação de movimentos na dança circular com pessoas com deficiência visual - Romao, Telma Sampaio (2011)
This paper aims at studying how circular dance can afford to sight-disabled peoples movement and how they can learn to cope with the deep movement of relation, consciousness, appropriation and communion with the world. Inside circular dance, a cosmic metaphor, is inscribed the movement of the world, which tells and changes amorously the human history. In the works of Paulo Freire and Maurice Merleau-Ponty one can find the necessary support to discuss, as long as possible, movement and existence. Research-action is used as a methodological approach whose empirical center is placed on the Institute of Education and Rehabilitation of Blind, in Natal, which shelters eight sightdisabled adults. The research s data reveal that the practice of circular dance concurs to enlarge the movement of the research s subjects, to develop a more accurate perception of their selves and of their own capacities, as well as improve the relations Me/Others, Me/World, which require a context of differences. The study has revealed that the practice of dance develops a better perception of the limits and surpasses as a human condition and, in consequence, the discovery of one s own body and the other s body as a resource of lessons and representations of the self and of the world. It lets out the development of a new way of thinking and coping with discrimination surrounding the disabled persons. In movement, in circular dance, the barrier between sight disablement and vision loses force.